Fostering Job Creation: Implementing Entrepreneurship Education in Senior High Schools - Wati, Sherly Octavia Mira; Sitorus , Onny Fitriana; Utami, Novelia (Edukasi, 2024)
Entrepreneurship is one of the relevant solutions to reduce unemployment by creating one's own jobs. Entrepreneurship education includes educational activities that promote entrepreneurial attitudes, cognition, and skills. This study aims to analyze how the implementation of entrepreneurship education is carried out in schools, and how the cultivation of attitudes, cognition, and skills is carried out by schools. This Research uses a qualitative method with a purposive sampling technique. Data collection techniques through interviews, observation, and documentation, with data validity using Triangulation of Sources and Triangulation of Techniques. Data analysis using Reducy data, Display data, and Conclusion. The results obtained from the Research are 1) Entrepreneurship education at school is one of the main factors for students in creating entrepreneurial products 2) The attitude instilled at school consists of sensitivity and creativity 3) The learning carried out using the Project and Training model carried out in collaboration with Prestasi Junior Indonesia 4) The benefits of entrepreneurship education in school students have the mental maturity to start a business when they graduate later and make entrepreneurship a student's career choice. SMA Negeri 81 Jakarta is a role model school that can be used as a driving force for surrounding schools, from elementary to high school, in creating superior school products.